The World Bank procurement regulations: a critical analysis of the enforcement mechanism and of the application of secondary policies in financed projects - Meireles, Marta de Castro (2006)
Many national and international instruments have been concerned with building an effective procurement system. In this context, particular procurement issues, such as the implementation of secondary policies, the review mechanism to address complaints, provisions on electronic procurement or rules governing privately financed projects, have received an in-depth examination. However, the particular analysis of those issues in the context of World Bank-funded procurement has been given almost no attention in the literature. Discussing such issues in the context of World Bank procurement involves special consideration because of the status and character of the organisation and the special nature of the relationship between the Bank, the borrower, and private parties involved in the procurement process.